2007
DOI: 10.1073/pnas.0705056104
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diversification and dispersal during periods of global warming by plethodontid salamanders

Abstract: A phylogeny and timescale derived from analyses of multilocus nuclear DNA sequences for Holarctic genera of plethodontid salamanders reveal them to be an old radiation whose common ancestor diverged from sister taxa in the late Jurassic and underwent rapid diversification during the late Cretaceous. A North American origin of plethodontids was followed by a continentalwide diversification, not necessarily centered only in the Appalachian region. The colonization of Eurasia by plethodontids most likely occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
238
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 207 publications
(252 citation statements)
references
References 53 publications
12
238
2
Order By: Relevance
“…The recent discovery of an Asian plethodontid from South Korea, Karsenia koreana (Min et al 2005), has helped to clarify the phylogenetic relationships and historical biogeography of Holarctic plethodontids. Molecular phylogenetic studies of these species have led to a reassessment of their taxonomy and phylogenetic relationships (Mueller et al 2004, Wiens et al 2005Vieites et al 2007). In conflict with traditional taxonomy (Wake 1966), molecular evidence from complete mitochondrial genomes and multiple nuclear loci identifies two distinct subfamilies: Plethodontinae and Hemidactyliinae ( Figure 1) (Vieites et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The recent discovery of an Asian plethodontid from South Korea, Karsenia koreana (Min et al 2005), has helped to clarify the phylogenetic relationships and historical biogeography of Holarctic plethodontids. Molecular phylogenetic studies of these species have led to a reassessment of their taxonomy and phylogenetic relationships (Mueller et al 2004, Wiens et al 2005Vieites et al 2007). In conflict with traditional taxonomy (Wake 1966), molecular evidence from complete mitochondrial genomes and multiple nuclear loci identifies two distinct subfamilies: Plethodontinae and Hemidactyliinae ( Figure 1) (Vieites et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular phylogenetic studies of these species have led to a reassessment of their taxonomy and phylogenetic relationships (Mueller et al 2004, Wiens et al 2005Vieites et al 2007). In conflict with traditional taxonomy (Wake 1966), molecular evidence from complete mitochondrial genomes and multiple nuclear loci identifies two distinct subfamilies: Plethodontinae and Hemidactyliinae ( Figure 1) (Vieites et al 2007). This study found that Karsenia is most closely related to members of the subfamily Plethodontinae.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of the genus Plethodon is particularly interesting given recent phylogenetic studies, which consistently nest the super-genus Desmognathus within a larger direct-developing clade that includes Plethodon (Chippindale et al, 2004;Mueller et al, 2004;Kozak et al, 2005Kozak et al, , 2009Macey, 2005;Vieites et al, 2007). These studies strongly suggest a reacquisition of larvae within the genus Desmognathus (see also Wake et al, 2011;Fig.…”
mentioning
confidence: 97%